EVALUATION OF MAHOGANY (Khaya senegalensis L.) STEM BARK POWDER FOR THE MANAGEMENT OF ROOT-KNOT NEMATODE (Meloidogyne spp.) ON COWPEA (Vigna unguiculata (L.) Walp) - Tijjni, Ibrahim; Abdullahi, N. (FUDMA JOURNAL OF SCIENCES, 2020)
A Field and screen house experiments were carried out to test the efficacy of mahogany (Khaya senegalensis L) bark powder at different concentration for the management of root-knot nematodes on cowpea. Its efficacy was compared with that of synthetic nematicide (cabofuran) as standard check. Twelve treatments were replicated four times in a completely randomized design. Each treatment was inoculated with 0 or 5000 eggs of Meloidogyne spp. extracted from the roots of highly susceptible garden egg (Solanum gilo) using 0.52 % a.i. sodium hypochlorite (NaOCl).Two replications were terminated at 60DAI to obtain data on number of galls and final nematode populations. Data were collected at 4, 6 and 8WAI on plant height, stem girth, number of days to 50 % flowering, number of pods/plant and number of seeds/pod. Data obtained were subjected to Analysis of Variance. Means were separated using Least Significant Difference at 5 % level of probability. Correlation analyses were performed on all the parameters assessed. Results obtained showed that 60g bark powder of the mahogany plant significantly (PË‚0.05) reduced the number of galls and population of the nematodes compared to the other treatments. The result also revealed that inoculated seedlings treated with 60g mahogany bark powder recorded higher value on plant height, stem girth, number of pods/plant, number of seeds /pod and seeds weight/plan when compared with other treatments and statistically significant at (PË‚0.05).Correlations between root galls, with plant height, stem girth, number of pods, plant, number of seeds/pod and seed weight/plant were negative and significant at
Keywords: Biopesticides, Mahogany, Organic Agriculture, Root-knot nematode